Optimizing Communication About Topical Corticosteroids: A Quality Improvement Study. Issue 3 (May 2020) - Johnson Girard, Valérie; Hill, Ashley; Glaser, Emma; Lussier, Marie-Thérèse
Background: Patients are often non-adherent to topical corticosteroids (TCS). This may be in part due to poor communication between patients and dermatologists. Objectives: This quality improvement (QI) study aims to describe dermatologist–patient communication about TCS treatments and to compare communication before and after the implementation of an educational intervention. Methods: This QI study assesses the communication between dermatologists and new dermatology outpatients receiving a TCS prescription in a tertiary care center. The QI intervention is 2-pronged, consisting of an educational pamphlet for patients and a communication workshop for the dermatology team. Encounters were audiotaped, and communication was analyzed using a coding system (MEDICODE). Phase 1 recordings happened preintervention and reflect the usual dermatologist–patient communication in this practice setting and phase 2 recordings were postintervention. Results: Phase 1 reveals that dermatologists frequently address informational medication themes, such as naming the medications and informing patients about their proper use. They less frequently discuss patient experience themes, such as goals of treatment, adverse effects of treatments, and exploring patients' emotions about medications (such as anxiety, fears, etc.). After the intervention, there was more frequent discussion of patient experience themes without increasing consultation length. But, in both phases, physicians address most themes as a monolog with little verbal input from patients. Conclusions: Our study raises awareness regarding dermatologists' communication patterns about TCS, identifying specific areas for improvement, such as discussions of adverse effects, and explicitly addressing patients' attitudes and emotions. This is an essential step to foster a sense-making of TCS for patients.